A meta-analysis of transformational leadership in hospitality research. Issue 6 (8th April 2020) - Gui, Chenglin; Luo, Anqi; Zhang, Pengcheng; Deng, Aimin
Abstract : Purpose: Though the effect of transformational leadership (TFL) on followers has been largely examined in hospitality, the findings are rather inconsistent. This paper aims to provide a quantitative review for the relationship between TFL and follower outcomes in hospitality and a detailed analysis of the moderating variables (cultural differences, measurement instrument, rating sources and time lag). Design/methodology/approach: To explore the effect sizes of TFL on followers, this study conducted a quantitative meta-analysis based on 62 primary studies, including 66 independent samples ( N = 23, 037). The outcomes of TFL were categorized into subordinates' attitudinal outcomes, relational perceptions and behavioral outcomes. Findings: The results indicate that TFL has the strongest impact on relational perceptions, followed by subordinates' attitudinal and behavioral outcomes. The results also show that cultural differences, rating sources and time lag partially moderate the relationships between TFL and follower outcomes. Research limitations/implications: TFL generally has a high level of validity for explaining attitudinal, behavioral and relational perception outcomes of followers in the field of hospitality. Given that, there have been a large number of studies investigating TFL with follower attitudinal and behavioral outcomes, it might not be necessary to continue applying identical frameworks to investigate the effect of TFL. Instead, future research on TFL is expected to explore the relationship between TFL and followers' relational perceptions and consider cultural and methodological factors. Originality/value: To the best of authors' knowledge, this is the first meta-analysis to clear theoretical links between TFL and its outcomes in the hospitality context. This study further investigates several moderators that can influence the effects of TFL and helps better understand the influence of TFL in the area of hospitality. The study also provides future research directions for leadership research in the hospitality context.